The Association Between Overweight or Obesity and the Risk of Uterine Leiomyoma: A Meta-Analysis - Jenabi, Ensiyeh; Khazaei, Salman; Aghababaei, Soodabeh; Soltani, Farzaneh (Current Women's Health Reviews, 2022)
Aim: The present study is a meta-analysis to identify the relationship between BMI and uterine leiomyoma. Methods: The major international databases PubMed, Scopus, and Web of Sciences (WOS) were searched to identify eligible studies in English language from their inception to 30 of June 2019. The pooled Odds Ratios (OR), Relative Ratio (RR), and 95% Confidence Intervals (CI) were calculated as random effect estimates of association among studies. The findings of 10 studies showed an increased risk of uterine leiomyoma in the overweight and obese women compared to women with normal weight: RR=1.21 (95% CI: 1.12, 1.30) and OR=1.50 (95% CI: 1.29, 1.71) for overweight women and RR=1.34 (95% CI: 1.11, 1.57) and OR=1.99 (95% CI: 1.11, 2.87) for obese women. Results: Our meta-analysis suggests that obesity and overweight in women are associated with an increase in the risk of uterine leiomyoma. Conclusion: Therefore, increased clinical attention to uterine leiomyoma should be given , because leiomyoma can be a source of mortality in women.
Keywords: Body mass index